Musashi 2 contributes to the stemness and chemoresistance of liver cancer stem cells via LIN28A activation. (1st January 2017) - Fang, Tian; Lv, Hongwei; Wu, Fuquan; Wang, Changzheng; Li, Ting; Lv, Guishuai; Tang, Liang; Guo, Linna; Tang, Shanhua; Cao, Dan; Wu, Mengchao; Yang, Wen; et al.
Abstract: Accumulating evidence suggests that cancer stem cells (CSCs), a small subset of cancer cells, are responsible for tumor initiation, progression, relapse and metastasis. Musashi 2 (MSI2), a RNA-binding protein, was proposed to be a potent oncogene playing key roles in myeloid leukemia and gastrointestinal malignancies. However, it remains elusive how MSI2 regulates stem cell features in HCC. Herein, we demonstrated that MSI2 was highly expressed in liver CSCs. Overexpression or knockdown of MSI2 altered CSC-related gene expression, self-renewal as well as resistance to chemotherapy in HCC cell lines. In mouse xenograft models, MSI2 could markedly enhance tumorigenicity. Mechanistically, overexpression of MSI2 resulted in the upregulation of Lin28A. Stemness and chemotherapeutic drug resistance induced by MSI2 overexpression were dramatically reduced by Lin28A knockdown. Moreover, MSI2 and LIN28A levels positively correlated with the clinical severity and prognosis in HCC patients. In conclusion, MSI2 might play a crucial role in sustaining stemness and chemoresistance of liver CSCs via LIN28A-dependent manner in HCC. Our findings revealed that MSI2 and Lin28A might be used as potential therapeutic targets for eradicating liver CSCs. Highlights: High expression of MSI2 in liver cancer and cancer stem cells. MSI2 is well correlated with OV6 expression and poor prognosis in liver cancer. To validate the close relation between MSI2 and LIN28A. MSI2 promotes stemness and chemoresistance of liver cancer stem cells via LIN28A-dependent manner.